THE FEMALE VOICE IN PATRIARCHAL WORLDS: COMPARING PREMCHAND AND BINA BARUAH - Das, Namita (ShodhKosh: Journal of Visual and Performing Arts, 2021)
Indian fiction has witnessed the emergence of novelists who have profoundly shaped readers’ understanding of societal structures, human emotions, and moral dilemmas. Among these luminaries, Munshi Premchand, often hailed as the King of Novelists in India, and Birinchi Kumar Baruah, writing as Bina Baruah, form a compelling pair for comparative exploration. Both authors, though writing in different linguistic and cultural milieus, exhibit a remarkable capacity to render the intimate experiences of women under patriarchal constraints. This seminar focuses on two of their representative works- Nirmala by Premchand and Jibanar Batot by Baruah examining how these novels articulate themes of suffering, endurance, duty, and the quest for dignity within the confines of societal expectations. By juxtaposing these texts, this study aims to highlight the universal resonance of female subjectivity portrayed by male authors and to underscore the socio-cultural dynamics that shape their narratives.